CUSTOMER EXPERIENCE AND WORD OF MOUTH COMMUNICATION (WOMC) IN INTER-STATE BRANDED TRASPORT COMPANIES: MEDIATING ROLE OF BRAND SATISFACTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2018)
The conceptualisation and delivery of memorable experience to tourists in the tourism industry has become a source of competitive advantage  for tourism service providers. This current  study examined  the direct and indirect effect of customer experience on word of mouth communication in the transportation sector of the tourism industry in the garden city of Port Harcourt, Rivers State, Nigeria. The descriptive  survey research gathered data from 150 inter-state passengers who commute with branded transport companies in Port Harcourt. A well structured questionnaire containing 12 items, with four demographic items was used to generate data from the respondents. The model  developed for the study was validated with the help of SPSSafter data editing, with  reliability analysis of the instrument and inferential statistics. The result of the inferential statistical analysis revealed that word of mouth  towards the branded transport companies is driven by customer experience. The mediating role of brand satisfaction also exists significantly between customer experience and word of mouth communication. The study concludes by positing that the delivery of memorable customer experience is capable of delighting passengers and thus promote positive passengers’ behavioural outcomes such as positive word of mouth. Transport service providers and their managers are expected to build capabilities in the area of experiential value conceptualisation and delivery based on pre-determined needs and expectations of their passengers who constitute thetarget market. Academic and professional implications are provided.